Investigation of the mathematical model of volumetric hydraulic drive with relay control as applied to the cargo crane winch - Zayarny S.L.; Baranov K.A. (Научно-технический вестник Брянского государственного университета)
The known variants of volumetric hydraulic drives of lifting and technological mechanisms are considered and analyzed. The areas of application of pumping and accumulator hydraulic drives, with various types of regulation, and options for their implementation as drives of a cargo winch of a bridge crane are considered. It is shown that the operation of the volumetric hydraulic drives of the cargo winch, along with volumetric and throttle control, can be performed by a relay method. It is noted that the cyclical operation of lifting mechanisms during lifting and lowering of cargo allows for mechanical and hydraulic energy recovery within the working cycle, which is a promising way to significantly increase the efficiency of their work. The analysis of the existing designs of hydraulic drives of technological machines, allowing to recover the potential energy of working bodies with cargo, is carried out. It is proposed as an alternative to the known hydraulic drives of the cargo winch of the bridge crane, a hydraulic drive with relay control. The efficiency of such a drive is shown, according to the indicators of the nominal pressure utilization coefficient and the energy intensity of the working fluid, in the case of the implementation of mechanical and hydraulic energy recovery in the working cycle in it. The mechanical and hydraulic circuits of such a drive are examined. An algorithm of mathematical model of its operation with consideration of different phases of cargo movement is proposed and its investigation is carried out. The possibility of fulfilling the safety conditions of operation of a hydraulic drive with relay control, in terms of ensuring the requirements for the uniformity of cargo movement, is analyzed.